Quantifying guideline adherence in mucormycosis management using the EQUAL score. Issue 4 (20th January 2020) - Koehler, Philipp; Mellinghoff, Sibylle C.; Stemler, Jannik; Otte, Felix; Berkhoff, Ariana; Beste, Nedim; Budin, Sofia; Cornely, Florian B.; Evans, Johanna M.; Fuchs, Frieder; Pesch, Luca; Rebholz, Arvid W.; et al.
Summary: Objectives: Mucormycosis is a difficult‐to‐diagnose life‐threatening disease with high morbidity and mortality. Adherence to guidelines that lead through complex management and support clinical decisions is however rarely reported. By applying the EQUAL Score, our study evaluates the management of mucormycosis at the University Hospital of Cologne, Germany. Methods: We performed a retrospective chart review of patients with mucormycosis at the University Hospital of Cologne. Data collection comprised items for quality assessment in mucormycosis management according to the EQUAL Mucormycosis Score and economics. Results: Of 29 patients identified, 27 were documented retrospectively. Eight patients of 18 with neutropenia (>10 days) or receiving allogeneic stem cell transplantation (44.4%) received mould active prophylaxis. Chest CT was done in 21 patients (77.8%), while BAL and direct microscopy of BAL fluid was performed in 22 patients (81.5%), culture in 22 (81.5%) and fungal PCR in 24 (88.9%). First‐line treatment was liposomal amphotericin B in 19 patients (70.4%). Isavuconazole or posaconazole with therapeutic drug monitoring was used in four (14.8%) and in one patient (3.7%), respectively. In our cohort, crude mortality was 51.9% (n = 14) with a median survival time of 113 days. During the management of the 27 patients, 450 points (53.8%) of the maximum EQUAL Mucormycosis Score were achieved (median 15 points, range 6‐30). Conclusions: We observed management of mucormycosis aligning with current guidelines and hope to encourage other groups to use the EQUAL Score in routine clinical settings. Future studies will evaluate whether guideline adherence in mucormycosis management improves patient outcome.